2000
DOI: 10.1083/jcb.149.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Apoptotic Apoptosis Protease–Activating Factor 1 (Apaf-1) Has a Cytoplasmic Localization Distinct from Bcl-2 or Bcl-XL

Abstract: How Bcl-2 and its pro-survival relatives prevent activation of the caspases that mediate apoptosis is unknown, but they appear to act through the caspase activator apoptosis protease–activating factor 1 (Apaf-1). According to the apoptosome model, the Bcl-2–like proteins preclude Apaf-1 activity by sequestering the protein. To explore Apaf-1 function and to test this model, we generated monoclonal antibodies to Apaf-1 and used them to determine its localization within diverse cells by subcellular fractionation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 69 publications
7
102
1
Order By: Relevance
“…37 When subcellular fractions of Jurkat (nonadherent) cells were analysed by immunoblotting with commercial antibodies, FADD was found exclusively in the cytosolic fraction (Figure 4a). The purity of the fractions was verified by probing blots with antibodies to cytoplasmic proteins, such as the Golgi complex resident protein b-COP (cytoplasmic fraction Figure 4a) and Apaf-1 38 (cytoplasmic fraction Figure 4b), the nuclear protein PARP (nuclear containing fraction Figure 4b) and caspase-2, found in both compartments (Figure 4a, b) as reported previously. 39 Further fractionation of the cytoplasmic fraction from the adherent cell line HeLa to generate light membrane (LM) and soluble fractions (S) showed that FADD was present in the soluble fraction similar to Apaf-1 and a small amount of FADD in the light membrane fraction but none in the HM fraction where the nuclei are found (Figure 4b).…”
Section: Subcellular Localisation Of Faddmentioning
confidence: 54%
“…37 When subcellular fractions of Jurkat (nonadherent) cells were analysed by immunoblotting with commercial antibodies, FADD was found exclusively in the cytosolic fraction (Figure 4a). The purity of the fractions was verified by probing blots with antibodies to cytoplasmic proteins, such as the Golgi complex resident protein b-COP (cytoplasmic fraction Figure 4a) and Apaf-1 38 (cytoplasmic fraction Figure 4b), the nuclear protein PARP (nuclear containing fraction Figure 4b) and caspase-2, found in both compartments (Figure 4a, b) as reported previously. 39 Further fractionation of the cytoplasmic fraction from the adherent cell line HeLa to generate light membrane (LM) and soluble fractions (S) showed that FADD was present in the soluble fraction similar to Apaf-1 and a small amount of FADD in the light membrane fraction but none in the HM fraction where the nuclei are found (Figure 4b).…”
Section: Subcellular Localisation Of Faddmentioning
confidence: 54%
“…Furthermore, despite early reports to the contrary 20,21 it is now accepted that mammalian Bcl-2 homologs do not functionally interact with APAF-1. [22][23][24] Given these significant differences, it is intriguing that the antiapoptotic functions of both Bcl-2 and CED-9 involve the mitochondria. Indeed, the functions of the mammalian Bcl-2 family members and those of CED-9/EGL-1 overlap in a number of interesting ways: despite sharing only around 22% homology with CED-9, expression of Bcl-2 inhibits apoptosis in C.elegans, 25 and Bcl-2 expression was found to rescue the excess of apoptosis found in CED-9 loss-of-function worms.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 99%
“…The alternative view is based on the discovery that prosurvival C. elegans CED-9 prevents CED-3 caspase activation by blocking its adapter CED-4. Since Bcl-2 and its prosurvival relatives do not bind to Apaf-1 (mammalian homologue for CED-4) (17,18), mammalian Bcl-2-like molecules would have to interact with other adapters that activate ''initiator caspases'' other than caspase-9 (mammalian homologue for CED-3). Support for this idea comes from the observation that Bcl-2 over-expression inhibits apoptosis of haematopoietic cells in mice more potently than loss of Apaf-1 or caspase-9 (19).…”
Section: Bcl-2 Family Proteins: the Sentinels Of Life And Deathmentioning
confidence: 99%